The rendering of the old far right/ the origin and formation of Chega - Marchi, R. (Chega: The new Portuguese far right, 2025)
In the first two decades of the 21st century, a fourth wave of radical right parties in Europe has succeeded the three waves identified by Klaus von Beyme (1988). The latter were formed by the neofascist parties founded in the immediate aftermath of the Second World War by the defeated of 1945; the populist wave in the 1960s and 1970s that was critic of the fiscal pressure caused by the growth of the welfare state; and the antiimmigration wave from the 1980s onwards. The former of the 21st century – the fourth wave – is nowadays characterized by a marked Euroscepticism caused by disenchantment with the European integration project, the relevance of Islamophobia as a result of global terrorism, the rejection of anti-democratism and violent extremism (Goodwin 2019: 108). In this recent context, radical populist right-wing parties have consolidated and entered or supported national governments with center and right-wing mainstream partners. These parties are no longer mere challenger or niche actors, since they became institutionalized in their national party systems (Mudde 2016: 16).